Effects of Cathode Location and the Size of Anode on Anodal Transcranial Direct Current Stimulation Over the Leg Motor Area in Healthy Humans - Foerster, Águida S.; Rezaee, Zeynab; Paulus, Walter; Nitsche, Michael A.; Dutta, Anirban (Frontiers in Neuroscience, 2018)
Objective: Non-invasive brain stimulation such as transcranial direct current stimulation (tDCS) involves passing low currents through the brain and is a promising tool for the modulation of cortical excitability. In this study, we investigated the effects of cathode location and the size of anode for anodal tDCS of the right-leg area of the motor cortex, which is challenging due to its depth and orientation in the inter-hemispheric fissure. Methods: We first computationally investigated the effects of cathode location and the size of the anode to find the best montage for specificity of stimulation effects for the targeted leg motor area using finite element analysis (FEA). We then compared the best electrode montage found from FEA with the conventional montage (contralateral supraorbital cathode) via neurophysiological testing of both, the targeted as well as the contralateral leg motor area. Results: The conventional anodal tDCS electrode montage for leg motor cortex stimulation using a large-anode (5cmx7cm, current strength 2mA) affected the contralateral side more strongly in both the FEA and the neurophysiological testing when compared to other electrode montages. A small-anode (3.5cmx1cm at 0.2mA) with the same current density at the electrode surface and identical contralateral supraorbital cathode placement improved specificity. The best cathode location for the small-anode in terms of specificity for anodal tDCS of the right-leg motor area was T7 (10–10 EEG system). Conclusion: A small-anode (3.5cmx1cm) with the same current density at the electrode surface as a large-anode (5cmx7cm) resulted in similar cortical excitability alterations of the targeted leg motor cortex respesentation. In relation to the other stimulation conditions, the small-anode montage with the cathode positioned at T7 resulted in the best specificity.